ANALISIS KOMPARATIF FAKTOR YANG MEMPENGARUHI BELANJA DAERAH PADA KABUPATEN/KOTA DI PROVINSI JAWA TIMUR - Syalafudin Fahroni Setyawan, - (2019)
This research was conducted to examine the effect of General Allocation Funds, Special Allocation Funds and Regional Original Revenues on Regional Expenditures and conduct comparative analysis on Districts / Cities in East Java Province from 2015-2017. The sample in this study was selected using a purposive sampling technique to obtain as many as 27 districts / cities from 38 regencies / cities in East Java Province with an observation period of three years. The analysis technique used in this study is multiple linear regression with a significance level of 5%. The results of this study indicate that the value of Adjusted R Square is 0.749, which means the ability of the independent variable General Allocation Funds, Special Allocation Funds and Regional Original Income can explain Regional Expenditures by 74.9%. Based on the variable significance test partially, it shows that (1) the General Allocation Fund has a significant effect on the Regional Expenditure, (2) Special Allocation Fund does not have a significant effect on the Regional Expenditure, and (3) Regional Original Income has a significant effect on the Regional Expenditure